Analisis Fakta Cerita dalam Novel Angin Bersyair Karya Andrei Aksana sebagai Cerminan Realitas Sosial dan Psikologis Tokoh dalam Alur Naratif Fiksi Modern Indonesia - Ni Wayan Iciari Kori; I Nyoman Weda Kusuma; I Ketut Sudewa (STIKes Ibnu Sina Ajibarang, 2025)
The author constructs the story world through elements such as plot, character, and setting. These elements are interconnected and form a cohesive whole within the narrative. This study aims to examine and analyze the story elements in the novel Angin Bersyair by Andrei Aksana. The theoretical framework used in this research is Robert Stanton's structuralism theory. This research employs a descriptive qualitative approach. Data collection was carried out through literature study, using techniques such as reading the novel, highlighting and identifying data, classifying, selecting, compiling the data corpus, and organizing the data. The results of the analysis show that the novel Angin Bersyair by Andrei Aksana is constructed using a mixed plot structure, the setting is categorized into place, time, and atmosphere. The characterization includes both main and supporting characters. The mixed plot in the novel combines both progressive and regressive plot patterns, allowing the author to weave past and present events fluidly to enrich the narrative tension and emotional depth. The temporal shifts also reflect the psychological complexity of the main characters, especially in relation to themes of love, identity, and longing. The setting of place varies from urban environments that reflect modern social dynamics to more introspective or symbolic places that reveal the characters’ inner worlds. The time setting spans multiple periods, indicating a narrative that draws heavily on memory and personal transformation. The atmosphere often shifts between melancholic, romantic, and contemplative tones, aligning with the protagonist’s emotional journey. Character analysis reveals a strong central figure whose emotional struggles and internal conflicts are supported and contrasted by secondary characters, enriching the story’s multidimensionality. The protagonist is depicted with psychological depth, while the supporting characters serve as foils or catalysts for change. Overall, this research highlights how Angin Bersyair employs literary elements to construct a rich and emotionally engaging narrative grounded in structuralist principles.